Examining the relationship between non-suicidal self-injury and mental health among female Arab minority students: the role of identity conflict and acculturation stress - Meisler, Sahar; Sleman, Sheren; Orgler, Michal; Tossman, Inbal; Hamdan, Sami (Frontiers in Psychiatry, 2023)
Background and objective: Research suggests that individuals from minority backgrounds, including immigrants and ethnic minorities, may be at a higher risk for non-suicidal self-injury (NSSI). The aim of the present research is to examine the relationship between non-suicidal self-injury (NSSI) and acculturation stress, depression, and risk behaviors among Female Arab minority students. Methods: The sample analyzed consisted of 1,529 female Arab students (85.8% B.A. students, 14% M.A. students) aged 21-54 (M = 23, SD = 4.17). The participants completed self-reported questionnaires assessing NSSI engagement, identity conflict and acculturation stress, depression, and risky substance use behavior. Results: As expected, we found a positive and significant positive association between NSSI and identity conflict and acculturation stress. In addition, an Identity crisis and acculturation stress impact the effect of depression and risky substance use behaviors in engaging in self-injury. Namely, participants were more likely to engage in NSSI when they also experienced acculturation stress and exhibited depressive symptoms and tended to display risky substance use behavior. Conclusion: These findings provide evidence that the relationship between depression and NSSI may be stronger among individuals who experience higher levels of identity crisis. Implications for intervention and future research are briefly presented.